Heart of creation : the Mesoamerican world and the legacy of Linda Schele - Stone, Andrea Joyce (University of Alabama Press, 2002)
The core of this book focuses on the current study of Mayan hieroglyphics as inspired by the recently deceased Mayanist Linda Schele. As author or coauthor of more than 200 books or articles on the Maya, Schele served as the chief disseminator of knowledge to the general public about this ancient Mesoamerican culture, similar to the way in which Margaret Mead introduced anthropology and the people of Borneo to the English-speaking world.